Influence of fluoride on the bacterial composition of a dual-species biofilm composed of Streptococcus mutans and Streptococcus oralis. Issue 9 (20th October 2016) - Jung, Ji-Eun; Cai, Jian-Na; Cho, Sung-Dae; Song, Kwang-Yeob; Jeon, Jae-Gyu
Abstract: Despite the widespread use of fluoride for the prevention of dental caries, few studies have demonstrated the effects of fluoride on the bacterial composition of dental biofilms. This study investigated whether fluoride affects the proportion of Streptococcus mutans and S. oralis in mono- and dual-species biofilm models, via microbiological, biochemical, and confocal fluorescence microscope studies. Fluoride did not affect the bacterial count and bio-volume of S. mutans and S. oralis in mono-species biofilms, except for the 24-h-old S. mutans biofilms. However, fluoride reduced the proportion and bio-volume of S. mutans but did not decrease those of S. oralis during both S. oralis and S. mutans dual-species biofilm formation, which may be related to the decrease in extracellular polysaccharide formation by fluoride. These results suggest that fluoride may prevent the shift in the microbial proportion to cariogenic bacteria in dental biofilms, subsequently inhibiting the cariogenic bacteria dominant biofilm formation.